Evaluation of a Proenvironmental Intervention in Primary School students (10-13 age) from Castilla-La Mancha (Spain) - Torres, Belén (2021)
Introduction. The current environmental crisis reveals the need to act immediately from the field of environmental education from a very early age. This paper presents a case study that aims to verify the efficiency of an educational intervention to promote pro-environmental attitudes, perception of household recycling behaviors, and knowledge related to proper waste disposal. Method. By means of a field experiment with an intergroup design of two randomized groups (experimental and control), a questionnaire was conducted before and after a pro-environmental intervention in a classroom with 75 primary education students. Pro-environmental attitude, perception of household recycling behavior, and level of knowledge about waste disposal at home were evaluated. The reliability of the measures and the effectiveness of the intervention were analyzed using repeated-measures ANOVA. Results. The results reveal that, after the intervention, the experimental group (N = 38) –in comparison with the control group (N = 37)– increased its pro-environmental attitude, its perception of the household recycling behavior, and its level of knowledge about waste disposal; this would demonstrate the effectiveness of the conducted pro-environmental intervention. Discussion. The proposed educational intervention was designed to generate more knowledge of what could be called responsible ecological behavior, focused on recycling, being especially effective in increasing pro-environmental attitudes related to the eco-knowledge dimension.